The Role of Perceived Service Quality and Islamic Financial Literacy on Customer Loyalty In NTB Syariah Bank - Firdaus, Achmad; Amalia, Hani Khairo (International Journal of Islamic Business and Economics (IJIBEC), 2024)
Islamic banks need to develop strategies to increase customer loyalty. It prevents customers from switching to other banks and ensures business survival. This is especially true for Islamic regional banks with relatively homogeneous customer bases. This study investigates the impact of perceived service quality and Islamic financial literacy on customer loyalty in NTB Syariah Bank, which is recognized for its excellence in regional banking. Through purposive sampling, data is gathered via questionnaires from 85 respondents after filtering through 112 respondents and analysed using Structural Equation Modelling (SEM). Key findings reveal that service quality significantly influences customer loyalty, with empathy and tangibility emerging as crucial factors. Empathy is crucial in fostering positive customer experiences and building long-term relationships. A high level of tangibility can enhance customer confidence and satisfaction. Additionally, the study underscores the positive correlation between service quality, Islamic financial literacy, and customer loyalty. Practical implications highlight the importance of enhancing financial literacy and fostering trust in Islamic banking through regulatory support and educational initiatives. This research fills a gap in understanding regional bank practices and offers insights for tailored financial literacy programs in rural communities.